Migrant parents’ contributions to students’ negotiations of their educational futures: A case study at a Norwegian high school - Melnikova, Julia (International Journal about Parents in Education, 2023)
The educational futures students aspire to and make specific choices in shaping are formed in the encounter between school practices and family dispositions. More research is needed to understand whether and how migrant parents are invited to contribute to high school students’ negotiation of these possible futures. Drawing on observations and interviews with students and parents from a single-school case study, this article explores how migrant parents contribute to students’ decision making. Seen through a Bourdieusian lens, the logic of the high school education field sets boundaries around what is regarded as feasible and valuable parental involvement. Parents are experienced as acting indirectly through hints and suggestions. The study indicates that providing guidance is complicated by expectations of student autonomy. The findings warrant further research on school parental involvement practices that can support students’ negotiation of possible futures.